2020
DOI: 10.12739/nwsa.2020.15.4.1a0462
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study on Treatment of Domestic Wastewater by Natural Soil

Abstract: In recent centuries, issues such as efficient use of water resources, water quality and water supply have become important for many countries. Countries have focused on developing strategies that can protect water and using water in the most efficient way including treatment of wastewater. In addition, it has become important to provide sustainability of the natural treatment systems instead of complex and expensive wastewater treatment facilities that are rapidly developing. On the other hand, the researches … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…These results have provided the wastewater standards discharge values (e-Legislation no: 7221). Similar results have been reported elsewhere (Todt et al 2014;Karpuzcu et al 2020). Chun et al (2008) found that the influent water SS concentration was 184 mg/L, while the effluent water SS concentration was 6-17 mg/L.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…These results have provided the wastewater standards discharge values (e-Legislation no: 7221). Similar results have been reported elsewhere (Todt et al 2014;Karpuzcu et al 2020). Chun et al (2008) found that the influent water SS concentration was 184 mg/L, while the effluent water SS concentration was 6-17 mg/L.…”
Section: Resultssupporting
confidence: 90%
“…They stated that soil with a high concentration of contaminants would be difficult to compact and a lower density could be obtained compared to uncontaminated soil under the same compaction effort and environmental conditions. On the contrary, studies shows that the optimum water content decreases and the maximum dry density increases (Jedari & Hamidi 2015;Karpuzcu et al 2020).…”
Section: Standard Compaction Testmentioning
confidence: 99%
See 1 more Smart Citation